Enteroviruses in Acute Myocardial Infarction - A Gholoobi; MS Nabavinia; T Mohamadpoor; MS Alavi; Z Meshkat (Tehran University of Medical Sciences, 2012)
Background: Human enteroviruses (EVs) may have a role as a possible risk factor in the pathogenesis of MI. The aim of this study was to evaluate the presence of enterovirus genomic RNA in peripheral blood samples of patients with acute myocardial infarction (MI).Methods: We investigated the presence of enterovirus genomic RNA in the peripheral blood of 115 patients with acute MI hospitalized in the Coronary Care Unit of Imam Reza and Ghaem University Hospitals (Mashhad, Iran) by RT-PCR using the virus specific primers.Results: The subjects' mean (±SD) age was 63.5 (±9.4) years (range: 38-82) and 38.3 % of the subjects were female. Of 115 patient specimens, 3 (2.6%) were positive in RT-PCR.Conclusion: The prevalence of enterovirus in MI patients is considerable. More investigations are needed to determine the causal role of enteroviruses in MI.